Compare and evaluate some order reduction algorithms for high-order power systems - Nguyễn Thanh Tùng; Đào Huy Du; Vũ Ngọc Kiên (Journal of Military Science and Technology, 2022)
This paper introduces, compares and evaluates 4 model order reduction algorithms which are Balanced truncation (BT), H-infinity Balanced truncation (HINFBT), Hankel-Norm Approximation (HNA) and Iterative Rational Krylov (IRKA) for high-order power system models without stability. The authors apply these algorithms to reduce a system of order 66th to a system of order 10th and 25th. From the simulation results and the difference between the order reduction system and the original system, it can be seen that the BT algorithm gives the response in the time domain, the frequency domain closely follows the original system with the smallest error while IRKA differs the most among the 4 algorithms.. The HINFBT algorithm can directly reduce the order of unstable objects without system decay, and the HNA method retains the high energy Hankel degeneracy values ​​of the original system, thus preserving the stability of the original system.